Evaluation of the Tuberculosis Program Drug Management at the Pharmacy Installation of the Bengkulu Provincial Health Office - Kusumaningsih, Riyani; Satibi, Satibi; Yasin, Nanang Munif (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Tuberculosis is currently a public health problem both in Indonesia and internationally, so it is one of the Sustainable Development Goals (SDGs) for sustainable health development. Therefore, good drug management is needed. The purpose of this study is to determine the level of suitability of the tuberculosis program drug management process at the planning, distribution, and control stages in 2020 and 2021 compared to drug management quality indicators and determine the factors that affect it. This study was conducted in October–November 2022. Descriptive observational research methods with quantitative data were obtained retrospectively, and qualitative data were obtained through observation and interviews with selected resource persons by purposive sampling. The results showed that the planning, distribution, and control of tuberculosis drugs in the Bengkulu Provincial Health Office had not met the indicator standards, which were shown by seven indicators not in accordance with drug management standards, namely the accuracy of planning, ITOR, empty stock, less stock, safe stock, excess stock, and expired. There are six indicators that meet the standards: accuracy of distribution; level of availability of drug; organization; funding; information systems; and the amount of human resources. Influencing factors are a lack of coordination in planning, record keeping, and reporting, and a lack of operational funds and transportation tools for anti TB drugs distribution